A conceptual framework for adopting sustainability in greening the supply chains. Issue 4 (5th November 2014) - So, Stuart; Xu, Henry
The objective of this work is to strengthen organisations' commitment to using sustainable supply chain management (SSCM), an emerging practice, which involves intra- and inter-organisational activities underpinned by supply chain operations reference model. The study critically reviews 42 research articles in SSCM that leads to six research propositions and a theoretical model. The model comprises three categories of adoption factors, i.e., organisational dynamics, enabling technology and management systems. The study aims to provide the ground works for opening a new research avenue with a multidiscipline approach by linking organisational behaviour (OB) and operations management (OM) to explain supply chain sustainability.